2020
DOI: 10.1590/0047-2085000000268
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence and risk of internalizing and externalizing problems in adolescents living with relatives displaying substance use disorders

Abstract: Objective To investigate the association between exposure to domestic violence and increased risk of internalizing and externalizing problems and substance use among adolescents living with relatives with substance use disorder (SUD) at a low-income community of São Paulo, Brazil. Methods A cross-sectional study was conducted with 102 adolescents aged 12-17 years (M = 14.2, SD = 1.7) who were living with relatives suffering from SUD. Outcomes were measured using the Youth Self-Report (YSR), psychosocial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Due to this, a series of typologies were developed in the present work. In the first one, relational categories, the majority of the articles retrieved are included (20), belonging to 46 % of the total articles, in which topics such as Dating, Family, and schooling relationship of partners are grouped. In the second typology, Personal categories (12), with a percentage of 25 % topics such as behavior and the use of substances by adolescents.…”
Section: Results Of Aggression and Violence In The Ibero-american Con...mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this, a series of typologies were developed in the present work. In the first one, relational categories, the majority of the articles retrieved are included (20), belonging to 46 % of the total articles, in which topics such as Dating, Family, and schooling relationship of partners are grouped. In the second typology, Personal categories (12), with a percentage of 25 % topics such as behavior and the use of substances by adolescents.…”
Section: Results Of Aggression and Violence In The Ibero-american Con...mentioning
confidence: 99%
“…In the systematic review, it could be observed that the different studies emphasized: dating relationships with a general objective of the realization of tests for the study of violent relationships in adolescents in different cultural contexts (47); in behavioral research, the objective was to study the variables leading a young person to act violently and aggressively through instruments in the different environments in which they interacted (57); in family relationships, the purpose was to evaluate domestic relationships and how these affect the adolescent's life (20); in legal aspects, although there was very little research retrieved, this consisted of examining mental health in adolescents who were going through detention for some legal conflict (58); in peer schooling relationship, the primary emphasis was to detect school violence involving the parents in preventing further violent abuse (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ED and ID have a substantial overlap, as they share common aetiologies (18). For example, long-term externalising behaviours can lead to internalising symptoms later in life (19,20) and vice versa (21) and are highly correlated (22). Despite the comorbidity of ED and ID, distinctive pathways have been described for externalising disorders from ODD via CD to anti-social-personality disorder in adulthood (22).…”
Section: Introductionmentioning
confidence: 99%
“…-Parent Management Training (PMT): Parent management training is based on behavioural and social learning principles (20,21). PMT addresses problematic parent-child interactions, especially coercive family processes (33).…”
Section: Introductionmentioning
confidence: 99%